Roll-over cyclometalation: A versatile tool to enhance the catalytic activity of transition metal complexes - Leist, Marko; Schön, Florian (Journal of organometallic chemistry, 2018)
Roll-over cyclometalation is a special case of cyclometalation. While in classical cyclometalation, C,H-activation (deprotonation or oxidative addition) has to occur at the ligand to result in a metallacycle, in roll-over cyclometalation the ligand in principle has the chance to undergo chelating coordination without cleavage of a C-H bond (e.g. κ2-N,N′- vs. κ2-C,N-coordination at 2,2′-bipyridines). Nature thus can decide for which route shall be followed. In this review, the basic parameters for bringing a system into roll-over cyclometalation are discussed, followed by an overview on compounds that have been published in this field during the last years. The major emphasis of this review however is on applications of roll-over cyclometalation in catalysis, a rather new field in coordination and organometallic chemistry.
Gesehen am 26.02.2020